Custom Application Booking Information System at PT Mitra Tekno Nusantara: Sistem Informasi Pemesanan Aplikasi Custom Di PT Mitra Tekno Nusantara - Ridwan, Alfian Junior; Pantjarani, Ari; Hastomo, Mursid Dwi (Politeknik Harapan Bangsa Surakarta, 2024)
Information systems can provide strategic opportunities in facing business competition when implemented to support a business process. PT. Mitra Tekno Nusantara (PT. MTN) is a company engaged in the Information Technology sector that produces various kinds of software and hardware. The process of recording custom application order transactions that are still manual has weaknesses in terms of speed of recording transaction processes. In addition, the deadline on a project is rarely monitored so that there are projects whose progress exceeds the specified time target. This of course of course from customers. To fix this problem, the researcher proposes to design a website-based computerized system to manage custom application order transaction data at PT. MTN. The design of the custom application ordering information system that the author proposes is made using the PHP Native programming language and MySQL database. The proposed information system design uses the Software Development Life Cycle (SDLC) method with the Waterfall model. With the design of this custom application ordering system, it is hoped that it will make it easier for admins to record transaction data for custom application orders. In addition, it makes it easier for the project head to monitor the deadline date of each project being worked on.